Erythema nodosum after COVID-19 vaccine - B. Maranini; G. Ciancio; M. Corazza; F. Ruffilli; G. Galoppini; M. Govoni (PAGEPress Publications, 2022)
The current coronavirus disease 2019 (COVID-19) pandemic is a global challenge with strong medical and socioeconomic implications. Hopes have been placed in the development of various vaccines. As the vaccination campaign is in progress, adverse effects need to be monitored closely. Possible side effects range from minor events to more serious manifestations. In this article, we describe two cases of erythema nodosum (EN) after COVID-19 vaccination in two previously healthy female patients of 59 and 51 years, respectively. Most of the usual etiologies of EN were excluded by laboratory testing. EN was successfully treated with corticosteroids. Remarkably, in the first case, a relapse occurred 48 hours after the second dose of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine. In this case series, we describe two unusual occurrences of EN after vaccination with an mRNA COVID-19 vaccine and a viral vector vaccine, respectively, and we discuss the available related literature.